2016
DOI: 10.1128/aac.00744-16
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Daptomycin to Anionic Lipid Vesicles Is Reduced in the Presence of Lysyl-Phosphatidylglycerol

Abstract: The cytoplasmic membrane of Staphylococcus aureus contains ϳ20 mol% of the net cationic lipid lysyl-phosphatidylglycerol (LPG). Elevated fractions of LPG are associated with increased resistance to cationic antibiotics, including the lipopeptide daptomycin (DAP). Although the surface charge of the bacterial cytoplasmic membrane is altered by LPG, surface binding of DAP was found to be only moderately affected in anionic vesicles containing 20 mol% LPG. These results suggest that charge repulsion cannot fully e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Loss-of-function mutations in the PG synthase PgsA and gainof-function mutations in the lysyl-PG synthase MprF lead to a reduction in negatively charged PG in the membrane. PG is needed for daptomycin-membrane interaction and antibacterial activity (81,(84)(85)(86). Mutations in the cardiolipin synthase Cls2 are associated with daptomycin resistance in S. aureus, Enterococcus faecalis, and E. faecium (81).…”
Section: Discussionmentioning
confidence: 99%
“…Loss-of-function mutations in the PG synthase PgsA and gainof-function mutations in the lysyl-PG synthase MprF lead to a reduction in negatively charged PG in the membrane. PG is needed for daptomycin-membrane interaction and antibacterial activity (81,(84)(85)(86). Mutations in the cardiolipin synthase Cls2 are associated with daptomycin resistance in S. aureus, Enterococcus faecalis, and E. faecium (81).…”
Section: Discussionmentioning
confidence: 99%
“…Various biophysical studies using synthetic lipid vesicles have attempted to demonstrate this charge dampening mechanism, with somewhat equivocal results. Experiments using both labile (Danner, et al 2008) synthetic native LPG and its chemically stable analogue LPE have shown that although they attenuate AMP-induced membrane lysis, significant amounts of peptide remained bound to the lipid bilayers (Kilelee, et al 2010, Khatib, et al 2016. None of these studies, however, had considered the role of mild acidity as an activator of LPG-mediated membrane protection, through inducing increased LPG biosynthesis (Gould and Lennarz 1970), eliciting demonstrable attenuation of peptide binding (Rehal, et al 2017) and thus significant resistance to AMPs in S. aureus (Walkenhorst, et al 2013).…”
Section: Neutron Reflectivity Measurements On S Aureus Mimetic Floatmentioning
confidence: 99%
“…Similarly, MprF catalyzes the transfer of a lysyl group to phosphatidylglycerol causing a net increase in cell surface charge and reduced DAP binding (18). Although, it has also been postulated that this reaction affects DAP susceptibility by decreasing the availability of phosphatidylglycerol for DAP binding (24). In contrast, Efc employs a different strategy that involves redistribution of anionic phospholipid microdomains away from the septum, to divert DAP from critical septal targets; this mechanism is mediated by the LiaFSR cell-envelope-stress-response system in association with cardiolipin synthase ( cls ) (15, 25, 26).…”
Section: Introductionmentioning
confidence: 99%